(untitled) (Universal International Scientific Journal, 2026)
This article is dedicated to the scientific and practical exploration of the effectiveness of a heuristic task system in enhancing students’ oral activity. The study analyzes the integration of heuristic methods into the pedagogical process and their role in developing students’ independent thinking and communication skills. The article presents the principles of designing heuristic tasks, methods for their application in classroom practice, and criteria for assessing oral activity from a scholarly perspective. The findings demonstrate that heuristic approaches significantly contribute to the development of critical thinking, creative communication, and verbal skills among students, thereby improving the overall quality of educational interaction